Uncertainty and the Employment Dynamics of Small and Large Businesses - Vivek Ghosal; Yang Ye (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine the impact of uncertainty on employment dynamics. Alternative measures of uncertainty are constructed based on the survey of professional forecasters, and regression-based forecasting models for GDP growth, inflation, S&P500 stock price index, and fuel prices. Our results indicate that greater uncertainty has a negative impact on growth of employment, and the effects are primarily felt by the relatively smaller businesses; the impact on large businesses are generally non-existent or weaker. Our results suggest that to truly understand the effects of uncertainty on employment dynamics, we need to focus on the relatively smaller and entrepreneurial businesses. We discuss implications for the framing of economic policy.
Keywords: L11; D80; O30; G10; L40; 330; uncertainty; employment; small businesses; entrepreneurship; real-options; financing-constraints